Construct validity of the five facet mindfulness questionnaire in meditating and nonmeditating samples. - Baer, R; Smith, G; Lykins, E; Button, D; Krietemeyer, J; Sauer, S; Walsh, E; Duggan, D; Williams, J (2008)
Previous research on assessment of mindfulness by self-report suggests that it may include five component skills: observing, describing, acting with awareness, nonjudging of inner experience, and nonreactivity to inner experience. These elements of mindfulness can be measured with the Five Facet Mindfulness Questionnaire (FFMQ). The authors investigated several aspects of the construct validity of the FFMQ in experienced meditators and nonmeditating comparison groups. Consistent with predictions, most mindfulness facets were significantly related to meditation experience and to psychological symptoms and well-being. As expected, relationships between the observing facet and psychological adjustment varied with meditation experience. Regression and mediation analyses showed that several of the facets contributed independently to the prediction of well-being and significantly mediated the relationship between meditation experience and well-being. Findings support the construct validity of the FFMQ in a combination of samples not previously investigated.